2016
DOI: 10.9721/kjfst.2016.48.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Cirsium japonicum Extracts Show Antioxidant Activity and PC12 Cell Protection against Oxidative Stress

Abstract: The phenolic compounds, antioxidant activity and neuronal cell protective effect of Cirsium japonicum extract were evaluated in this study. High performance liquid chromatography mass analysis showed that C. japonicum was composed of chlorogenic acid, linarin, and pectolinarin. C. japonicum extract showed its antioxidant activity with halfmaximal inhibitory concentrations of 567 and 130 µg/mL by DPPH and ABTS radical scavenging activity, respectively. The total antioxidant capacities of C. japonicum via DPPH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…As we predicted, the antioxidant phenolic compounds in CJ showed protective effects in oxidative stressed PC12 cells and C. elegans. The current results showed that CJ extract diminished the ROS level, which is consistent with the previous study showing the fact that CJ reduced ROS level [4,7,38].…”
Section: Positive Effect Of Cj Extract On the Lifespan Of C Eleganssupporting
confidence: 93%
See 4 more Smart Citations
“…As we predicted, the antioxidant phenolic compounds in CJ showed protective effects in oxidative stressed PC12 cells and C. elegans. The current results showed that CJ extract diminished the ROS level, which is consistent with the previous study showing the fact that CJ reduced ROS level [4,7,38].…”
Section: Positive Effect Of Cj Extract On the Lifespan Of C Eleganssupporting
confidence: 93%
“…The antioxidant activities showed the same pattern of the results on their phenolic contents. Antioxidant activity has a positive correlation with phenolic contents [4,25]. Based on these results, the temperatures above 70 °C applied until a complete dry state could reduce the phenolic content consequently reducing antioxidant properties.…”
Section: The Effects Of Different Drying Methods On the Antioxidant Cmentioning
confidence: 69%
See 3 more Smart Citations